Selection of processing parameters in laser microwelding. Part 1: Continuous wave (CW) mode - Coroado, J.; Ganguly, Supriyo; Suder, Wojciech; Williams, Stewart; Martins Meco, Sonia; Pardal, Goncalo (Old City Publishing, 2020)
A phenomenological model which specifies the penetration depth and width of the fusion zone in laser microjoining can be a very useful tool in achieving the required welding parameters for a desired application. In this study the power factor model, previously established and validated in macrowelding, has been tested in fibre laser microwelding, enabling achievement of a particular weld independently of a laser system. Differ-ent weld profiles in aluminium and stainless steel were correlated with various combinations of parameters for a wide range of beam diameters. It has been shown that the same penetration depth can be achieved with different weld profiles. A similar trend, as previously found in macrow-elding, has been confirmed in microwelding. It was demonstrated that the depth of penetration can be kept constant independently of the laser sys-tem until certain limit of beam size.
Keywords: power factor model; weld shape; beam diameter; depth of penetration; interaction time; laser microwelding; 304L stainless steel; 5251 aluminium alloy; Fibre laser